Pengaruh Motivasi kepuasan Dan Komitmen Organisasi Terhadap Kinerja Pegawai Pada BPKP Perwakilan Sulawesi Selatan - Mattarima Mattarima; Muhtazib Muhtazib; Desi Usjay (GEMILANG: Jurnal Manajemen dan Akuntansi, 2021)
This study aims to determine the effect of motivation, satisfaction and organizational commitmen on employee peformance at the financialsupervisory agency and Representative Develoment of South Sulawesi. The methdot used in this study is a quantitative approach method. The population in this study were all BPKP employees. Makassar. The slovin technique whwre the population was a sample of 65 people, the data collection technique used a questionnaire. The collected data is processed using SPSS. Based on the conclusion that the monkhey motivation variabel (XI) has a significant effect on employee peformance (Y) partially proven by a sig valuae of 0.14<0,14. Work statisfanction (X2) has a significant effect on employee performance (Y) partially proven with a significant valuae of 0,46<0,05. The variable of organizational commitmen (X3) also has a significant effect on employee peformance (Y) partially proven by a significant valuae of 0.046< 0,05